Exploring the Abyss of Inequalities 4th International Conference on Well-Being in the Information Society, WIS 2012, Turku, Finland, August 22-24, 2012. Proceedings - Eriksson-Backa, Kristina; Luoma, Annika; Krook, Erica; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 4th International Conference on Well-Being in the Information Society, WIS 2012, held in Turku, Finland, in August 2012. The 13 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on e-health; measuring and documenting health and well-being; empowering and educating citizens for healthy living and equal opportunities; governance for health; safe and secure cities; information society as a challenge and a possibility for aged people.
Topical sections on e-health -- Measuring and documenting health and well-being -- Empowering and educating citizens for healthy living and equal opportunities -- Governance for health -- Safe and secure cities -- Information society as a challenge and a possibility for aged people.
Keywords: Computer science; Medicine; Computer Science; Computers and Society; User Interfaces and Human Computer Interaction; Information Systems Applications (incl. Internet).; Medicine/Public Health, general